2004
DOI: 10.1038/sj.gt.3302231
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of episomal transgene expression by plasmid bacterial DNA elements in vivo

Abstract: We previously demonstrated that sustainable enhanced levels of transgene products could be expressed from a bacterial DNA-free expression cassette either formed from a fragmented plasmid in mouse liver or delivered as a minicircle vector. This suggested that bacterial DNA sequences played a role in episomal transgene silencing. To further understand the silencing mechanism, we systematically altered the DNA components in both the expression cassette and the bacterial backbone, and compared the gene expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
198
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(208 citation statements)
references
References 38 publications
9
198
0
1
Order By: Relevance
“…Bacterial DNA sequences on conventional plasmids cause transcriptional silencing, whereas sustained transgene expression may be obtained following transfer of minicircles. [19][20][21]39 The persistence of transgene expression following hydrodynamic transfer of minicircles and the sharp Adenoviral and hydrodynamic transfer F Jacobs et al decline of expression after transfer of plasmids in the current study was also observed when hydrodynamic transfer was performed with an identical dose of 50 mg. Thus, the difference in kinetics of transgene expression after hydrodynamic transfer of plasmids and minicircles in Figure 3a cannot be attributed to dose difference.…”
Section: Adenoviral and Hydrodynamic Transfermentioning
confidence: 49%
See 1 more Smart Citation
“…Bacterial DNA sequences on conventional plasmids cause transcriptional silencing, whereas sustained transgene expression may be obtained following transfer of minicircles. [19][20][21]39 The persistence of transgene expression following hydrodynamic transfer of minicircles and the sharp Adenoviral and hydrodynamic transfer F Jacobs et al decline of expression after transfer of plasmids in the current study was also observed when hydrodynamic transfer was performed with an identical dose of 50 mg. Thus, the difference in kinetics of transgene expression after hydrodynamic transfer of plasmids and minicircles in Figure 3a cannot be attributed to dose difference.…”
Section: Adenoviral and Hydrodynamic Transfermentioning
confidence: 49%
“…19,20 Minicircles are devoid of bacterial sequences and may induce persistent transgene expression. 19,21 Previous studies of our group comparing the potency of different expression cassettes have shown that the combination of the 1.5 kb hepatocyte-specific human a 1 -antitrypsin (AT) promoter and four copies of the human apo E enhancer (E 4 ) results in superior expression levels compared to the ubiquitously active cytomegalovirus (CMV) promoter, the ubiquitously active murine U1b small nuclear RNA promoter and the combination of the apolipoprotein (apo) A-I or apo C-II promoter and four copies of the human apo E enhancer. 1,8,[22][23][24] In these studies, the promoter was placed upstream of the four exons and three introns of the human apo A-I gene.…”
Section: Introductionmentioning
confidence: 99%
“…The removal of bacterial sequences from the transgene expression unit for human factor IX and a1-antitrypsin resulted in highly significant increases in protein level and duration of expression in another study by Chen et al 7 In this work, minicircle vectors devoid of bacterial sequences were prepared using a unidirectional fC31 phage recombinase system. When the minicircles were hydrodynamically injected, 45-and 560-fold higher factor IX and a1-antitrypsin levels were achieved, respectively, at 3 weeks post-transfection compared to the bacterial plasmids.…”
Section: Prospectsmentioning
confidence: 98%
“…Photoreceptor cell transduction or transfection by early adenovirus, 11 HIV-based lentiviruses 12,13 or various non-viral methods 3 is relatively inefficient, and the duration of transgene expression limited either by silencing of the transgene promoter 14 or through clearance of transduced cells after immune responses to vector proteins. 15 Further development of these vector systems, for example, by the removal of immunogenic viral genes from the vector genome of adenovirus 16 or the removal of bacterial plasmid sequences in DNA mini-circles in non-viral gene transfer 17 has resulted in significant improvements in longevity of expression.…”
Section: Gene Transfer To Photoreceptor Cellsmentioning
confidence: 99%